1987
DOI: 10.2105/ajph.77.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing among young Latino women in the United States.

Abstract: IntroductionThe past decade has seen a spate of research studies and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 1 publication
3
21
0
2
Order By: Relevance
“…Specifically acculturated Latinas are more likely than are less acculturated Latinas to engage in nonmarital sexual activity and have multiple partners. 18,[21][22][23][24][25] For example, in 1 study, 41% of third-generation Mexican American women reported that they had engaged in sexual intercourse, compared with 18.5% of first-generation Mexican American women. 23 Among never-married Hispanic women aged 15 to 24 years, higher levels of acculturation (indexed by use of English vs Spanish language) significantly predicted young women's sexual activity during the past year.…”
Section: Acculturation Status and Sexuality Among Female Cuban Americmentioning
confidence: 97%
See 3 more Smart Citations
“…Specifically acculturated Latinas are more likely than are less acculturated Latinas to engage in nonmarital sexual activity and have multiple partners. 18,[21][22][23][24][25] For example, in 1 study, 41% of third-generation Mexican American women reported that they had engaged in sexual intercourse, compared with 18.5% of first-generation Mexican American women. 23 Among never-married Hispanic women aged 15 to 24 years, higher levels of acculturation (indexed by use of English vs Spanish language) significantly predicted young women's sexual activity during the past year.…”
Section: Acculturation Status and Sexuality Among Female Cuban Americmentioning
confidence: 97%
“…In keeping with this view, most empirical studies of Latina sexual behavior use language as a measure of acculturation 17,18,24,25 (1 used generation of immigration 23 and another birthplace 21 ). However, these measures may not fully capture the complexities of the acculturative process.…”
Section: Acculturation Status and Sexuality Among Female Cuban Americmentioning
confidence: 99%
See 2 more Smart Citations
“…[105][106][107][108][109][110][111][112][113] Although significant progress has been made in the identification and collection of data on Latino health, several methodologic limitations hinder researchers'ability to fully capture disease and disability trends among Latino subgroups. 6,13,14,119 These limitations include the following: aggregation of all Hispanics into one group for analysis, without precise measurement of socioeconomic status; limited reporting of age and sex breakdowns, especially in studies of Latino children; and exclusion of Spanishspeaking populations, predominantly immigrants, because most national survey instruments are published in English.…”
Section: Pitfalls In Latino Subgroup Data Collectionmentioning
confidence: 99%